Hubungan Tingkat Stres Dan Imt Dengan Siklus Menstruasi Pada Mahasiswi Prodi Kebidanan Program Sarjana Universitas Respati Yogyakarta - Handayani, Fika; Ratnaningsih, Ester; Ayu Wantini, Nonik (Awatara Publisher, 2023)
Background: Menstruation is regular uterine bleeding as a sign that the reproductive organs are functioning properly. Various factors, including nutritional status, stress, physical activity, adequacy of macronutrients, and endocrine disorders, influence a woman's menstrual cycle. However, two main factors related to the menstrual cycle are nutritional status and stress. The results of a preliminary study showed that 70% of 10 female students experienced menstrual cycle disorders.Objective: This study aimed to examine how stress levels and BMI were linked to menstrual cycle disorders among the Undergraduate Program in Midwifery students at Respati University of Yogyakarta.Methods: This study was analytic observational research conducted using a cross-sectional design with a sample of 97 people. The data collection instruments comprised questionnaires, tread scales, and microtoise. The statistical test was done using the Chi-Square test.Results: Most female students experienced stress (66%), had normal Body Mass Indexes (63.9%), and had normal menstrual cycles (80.4%). There was no correlation between the participants' stress levels and menstrual cycles (p=0.603) nor between their BMI and menstrual cycle (p=1.000).Conclusion: The students’ stress levels and BMI did not correlate with their menstrual cycles